#PLLQueerTheory: Fans' reactions to queer representation in Pretty Little Liars. (1st June 2020) - Day, Sara K.; Pennell, Summer Melody
Pretty Little Liars is a television show popular with queer teen adolescent girls and emerging adult women who engage in conversation on Twitter. In this case study centred on the queer relationship between main characters Emily and Alison, the authors employ fandom studies and queer theory to analyse tweets about the show using the popular hashtags #Emison and #BooRadleyVanCullen. Findings reveal that queer young women used Twitter both to praise and critique the relationship and its homonormative constructs, resist heteronormativity surrounding the portrayal of Emily's sexuality in particular, and create a sustainable queer community.